The secret garden ebook - Burnett, Frances Hodgson (Duke Classics, 2012)
Mary Lennox is born in India. She is a sickly, sallow child, whose parents hide her away with her Ayah. After her parents die in a cholera outbreak she is sent to live in Yorkshire with her uncle. She is, once more, left mostly to herself. Her uncle still mourns his beautiful wife ten years after her death, and seeks to escape his grief by traveling. When a chambermaid tells Mary about her mistress's garden, which her master locked up on her death, Mary is determined to find it. Bit by bit, as the garden comes back to life, so do the lives of those around her begin to mend.